2018
DOI: 10.1002/lary.27610
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported versus physiologic swallowing outcomes in patients with head and neck cancer after chemoradiation

Abstract: Objective The primary objective of this project was to retrospectively investigate the relationship between patient‐reported and physiologic swallowing measures after chemoradiation therapy for head neck cancer (HNC). Methods Adult patients who underwent chemoradiation therapy for HNC and presented for videofluoroscopic swallow study were reviewed retrospectively. Surgically treated patients were excluded. Patient perception of swallowing‐related outcomes was assessed via the MD Anderson Dysphagia Inventory (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 24 publications
(68 reference statements)
1
35
0
2
Order By: Relevance
“…It is therefore incumbent upon clinicians to be quite thoughtful about the selection of survey instruments. As has been noted by many previous authors, PROMs currently used in laryngology are not necessarily optimal, either from a practical or psychometric perspective; they are not always correlated with objective measures and are designed to provide complementary information to standard clinical assessment . Furthermore, there are significant patient and physician factors that hinder the usefulness of PROMs, related to survey administration, impatience, and other underlying biases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore incumbent upon clinicians to be quite thoughtful about the selection of survey instruments. As has been noted by many previous authors, PROMs currently used in laryngology are not necessarily optimal, either from a practical or psychometric perspective; they are not always correlated with objective measures and are designed to provide complementary information to standard clinical assessment . Furthermore, there are significant patient and physician factors that hinder the usefulness of PROMs, related to survey administration, impatience, and other underlying biases.…”
Section: Discussionmentioning
confidence: 99%
“…As has been noted by many previous authors, 8,9,42 PROMs currently used in laryngology are not necessarily optimal, either from a practical or psychometric perspective; they are not always correlated with objective measures and are designed to provide complementary information to standard clinical assessment. 48 which is a critical measure in development of such tools and was explicitly not studied herein, can be difficult to measure given the dynamic nature of voice complaints, which may vary over a short period of time. Clinicians using PROMs in all areas of otolaryngology, and medicine in general, are encouraged to consider the validity and reliability of this data prior to accepting and using a measure.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Also, dysphagia has been found to be one of the most commonly reported late side effects after radiotherapy, 16,18 with 45% of patients reporting it 2 years after IMRT. [19][20][21][22] Motz et al observed the highest incidence of dysphagia, airway obstruction, and pneumonia in the first year after treatment but without a significant decrease in the subsequent four years. 9 Limited studies have assessed toxicity >2 years after therapy.…”
Section: Introductionmentioning
confidence: 99%
“…9 Limited studies have assessed toxicity >2 years after therapy. 20 Furthermore, Patterson et al found that 71% of patients 6 years post-IMRT reported swallowing problems, of whom one-fifth suffered from aspiration. 22 The study by Kirsh et al assessed very late dysphagia (>3 years after IMRT) and saw that 23% of the patients still required a modified diet after a mean follow-up time of 4.55 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation